2015
DOI: 10.1371/journal.pone.0125727
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Arctigenin-Induced Specific Cytotoxicity against Human Hepatocellular Carcinoma Cell Lines: Hep G2 and SMMC7721

Abstract: Arctigenin (ARG) has been previously reported to exert high biological activities including anti-inflammatory, antiviral and anticancer. In this study, the anti-tumor mechanism of ARG towards human hepatocellular carcinoma (HCC) was firstly investigated. We demonstrated that ARG could induce apoptosis in Hep G2 and SMMC7721 cells but not in normal hepatic cells, and its apoptotic effect on Hep G2 was stronger than that on SMMC7721. Furthermore, the following study showed that ARG treatment led to a loss in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Next we observed that NFAT5 promotes apoptosis via regulating PARP-1, BAX and BCL-2, essential biomarkers of apoptosis. PARP-1 is the downstream of BAX/BCL-2 in apoptotic pathway [9,18]. PARP-1 has been demonstrated to contribute DNA base excision repair and maintenance of genomic stability [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next we observed that NFAT5 promotes apoptosis via regulating PARP-1, BAX and BCL-2, essential biomarkers of apoptosis. PARP-1 is the downstream of BAX/BCL-2 in apoptotic pathway [9,18]. PARP-1 has been demonstrated to contribute DNA base excision repair and maintenance of genomic stability [19].…”
Section: Discussionmentioning
confidence: 99%
“…Poly (ADP-ribose) polymerase 1 (PARP-1), BAX/BCL-2 are considered as great important biomarker of apoptosis. During apoptosis, PARP-1 is cleaved into an 85 kDa fragment, which has the real function to initiate downstream signals [9]. BAX is a protein leading to apoptosis while BCL-2 is a protein function as anti-apoptotic factor.…”
Section: Nfat5 Expression Was Lower In Hcc Tissue Than Nontumor Tissuementioning
confidence: 99%
“…Adriamycin (ARG) has been currently recognized as a multifunctional chemotherapeutic drug with anti-inflammatory, anti-viral, anti-cancer, and other functions [80]. The data from Lu et al [81] showed that apoptosis in HepG2 cells and Smmc7721 cells could be induced by Adriamycin via activation of the Caspase-8 signaling pathway, up-regulation of Fas/FasL expression, and increasing the secretion of TNF-alpha. The apoptotic effect of the former was significantly stronger than that of the latter.…”
Section: Fasl Expressed On Nk Cells Exerts Anti-hepatocarcinoma Activmentioning
confidence: 99%
“…Caffeic acid increases collagen production, in addition to having antiaging, antioxidant, antimicrobial, antiatherosclerotic, antidiabetic, antitumor, anti-inflammatory, and photo-protective properties (Dhingra & Chhillar, 2012;Gugliucci, Bastos, Schulze, & Souza, 2009;Magnani, Isaac, Correa, & Salgado, 2014;Oksana et al, 2012). Studies have shown that arctigenin has antioxidant, antitumor, anti-inflammatory, antiviral, analgesic, neuroprotective, and memoryenhancing activities (Chakraborty & Borah, 2013;Du et al, 2016;Lu et al, 2015;Park, Hong, Moon, Kim, & Kim, 2011;Srivastava & Shukla, 2015;Zhu et al, 2013). Retusin is an antiemetic, antitumor, and psychoactive agent; and teas containing it are used as anti-inflammatory agents, analgesics, purgative, laxative, and cathartic (Chakrapani et al, 2013;Chapman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%